New Approach to create an Effective Natural Treatments of Infections caused by Human Papillomavirus - Momir Dunjic; Stefano Giuseppe Turini; Slavisa Stanisic; Nenad Sulovic; Sasa Cvetkovic; Dejan Mihajlovic; Marija Dunjic; Dusan Simic; Katarina Dunjic (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Human Papillomavirus (HPV) has a double-stranded DNA (dsDNA) genome. Infections, mainly sexually transmitted, usually resolve spontaneously. However, if the infection persists over time, lesions of the skin and mucous membranes tend to appear, notably mucosal lesions in the cervix or the appearance of warts. Some of those slowly progress to cancers such as cervical, oral, anus, esophagus, and larynx carcinoma. Diagnosis of an HPV infection is made by Papanicolaou test (Pap test) or molecular screening such as the HPV DNA Test. Treatment with natural products is based on essential oils. The main point of this work is to identify natural molecules from vegetal derivation capable of inhibiting the proliferation of HPV-16 with the same and/or superior affinity as regular drugs used in pharmacological treatment. Once we have identified the main components in these plants, we have applied molecular docking software 1-Click Docking, for virtual testing of those, on main antigenic determinants of HPV-16 as oncoproteins E6 and E7 as well as major capsid protein L1. The major active component to bind oncoprotein E6, apigenin, has shown an affinity bigger than other molecules. For major capsid protein L1, apigenin has shown one level of affinity similar to conventional drugs. These results have shown how it is possible, with natural products present in our daily lives, to inhibit the proliferation of HPV.